Paroxysmal nocturnal hemoglobinuria (PNH) and primary p.Cys89Tyr mutation in CD59: Differences and similarities. Issue 1 (September 2015) - Mevorach, Dror
Highlights: CD59 deficiency is a common finding in patients with paroxysmal nocturnal hemoglobinuria (PNH). We have recently described a Cys89Tyr CD59 mutation that have similarities and differences to PNH. The CD59 mutation was manifested in infancy in hemolysis and peripheral demyelinating disease. Abstract: CD59 encodes a 77 amino acid glycosylphosphatidylinositol (GPI)-anchored cell surface glycoprotein that inhibits the final step of membrane attack complex (MAC) formation. CD59 deficiency is a common finding in adult patients with paroxysmal nocturnal hemoglobinuria (PNH). In this condition, there is a clonal expansion of hematopoietic stem cells that have acquired a mutation in the PIGA gene (phosphatidylinositol glycan anchor biosynthesis, class A). PIGA encodes a GPI biosynthesis protein, phosphatidylinositol N-acetylglucosaminyltransferase subunit A, and erythrocytes deficient in GPI-anchored membrane proteins, including CD59, undergo complement-mediated hemolysis. We have recently described a primary homozygous Cys89Tyr CD59 deficiency in humans that resulted in the amino acid substitution p.Cys89Tyr with resulting failure of proper localization of the CD59 protein to the cell surface. The Cys89Tyr mutation in CD59 was clinically manifested in infancy, and associated with chronic hemolysis and relapsing peripheral demyelinating disease resembling recurrent Guillain–Barré syndrome (GBS) or chronic inflammatory demyelinating polyneuropathy (CIDP). In this review we describe differences and similarities in the pathogenesis and clinical manifestations of PNH and primary CD59 Cys89Tyr mutation with the aim of tracking the contribution of CD59 deficiency to the pathophysiology and perhaps deepening our understanding of both diseases.